2016
DOI: 10.1038/ncomms11313
|View full text |Cite
|
Sign up to set email alerts
|

Low excitatory innervation balances high intrinsic excitability of immature dentate neurons

Abstract: Persistent neurogenesis in the dentate gyrus produces immature neurons with high intrinsic excitability and low levels of inhibition that are predicted to be more broadly responsive to afferent activity than mature neurons. Mounting evidence suggests that these immature neurons are necessary for generating distinct neural representations of similar contexts, but it is unclear how broadly responsive neurons help distinguish between similar patterns of afferent activity. Here we show that stimulation of the ento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
100
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(108 citation statements)
references
References 59 publications
(140 reference statements)
7
100
1
Order By: Relevance
“…Although very young hippocampal neurons fire less specifically and with a reduced latency than older neurons [Schmidt-Hieber et al, 2004;Marin-Burgin et al, 2012;Danielson et al, 2016], perhaps there is an intermediate age during which new, but mature, neurons are better able to achieve the precise firing accuracy necessary for ultrasparse coding compared with aging neurons. Alternatively, or in addition, perhaps young neurons in HVC maintain sparse coding, despite high intrinsic excitability, by balancing broad responsivity with low network connectivity as demonstrated recently in the hippocampus [Dieni et al, 2016]. Therefore, birds with greater numbers of new HVC-RA neurons are better able to maintain the precision necessary for song stereotypy.…”
Section: New Neurons In the Song Motor Pathway Hvc: A Role For New Nementioning
confidence: 94%
See 1 more Smart Citation
“…Although very young hippocampal neurons fire less specifically and with a reduced latency than older neurons [Schmidt-Hieber et al, 2004;Marin-Burgin et al, 2012;Danielson et al, 2016], perhaps there is an intermediate age during which new, but mature, neurons are better able to achieve the precise firing accuracy necessary for ultrasparse coding compared with aging neurons. Alternatively, or in addition, perhaps young neurons in HVC maintain sparse coding, despite high intrinsic excitability, by balancing broad responsivity with low network connectivity as demonstrated recently in the hippocampus [Dieni et al, 2016]. Therefore, birds with greater numbers of new HVC-RA neurons are better able to maintain the precision necessary for song stereotypy.…”
Section: New Neurons In the Song Motor Pathway Hvc: A Role For New Nementioning
confidence: 94%
“…It may be that the role of new neurons in this region with respect to plasticity and stability is biphasic. The heightened plasticity and low response latency of immature neurons [Schmidt-Hieber et al, 2004;Marin-Burgin et al, 2012] coupled with sparse coding [Dieni et al, 2016] may be characteristics best suited for encoding new memories. Once incorporated into the memory trace, the activity of mature new neurons may serve to stabilize the memory trace.…”
Section: New Neurons In the Hippocampus May Subserve Both Plasticity mentioning
confidence: 99%
“…These data are in keeping with previous observations showing a sparse recruitment of DGCs during a spatial behavioral experience (Chawla et al, 2005). Remarkably, we showed that, in our experimental conditions, activated DGCs display features of mDGCs since (i) the examination of their radial distribution across the cell layer revealed a majority of fosGFP + cells located near the molecular layer, (ii) we did not observe cells that were co-labelled with EGFP and DCX antibodies, and (iii) they exhibited a mean value of Rin characteristic of mature DGCs (Overstreet-Wadiche and Westbrook, 2006; Dieni et al, 2016; Save et al, 2019). These observations reinforce the notion that mDGCs are not dormant cells (Alme et al, 2010) but comprise active neurons involved in specific tasks (Nakashiba et al, 2012; Vukovic et al, 2013).…”
Section: Discussionmentioning
confidence: 59%
“…In line with this hypothesis, Dieni et al showed that low excitatory innervation balanced high excitability of immature neurons in the dentate gyrus and prevented broad responsiveness of these neurons. 24 Although this hypothesis cannot be ruled out, according to our data, the number of GABAergic synapses increased as much as the number of dendritic spines in NL2A-overexpressing post-natal-born neurons, suggesting that the inhibitory/ excitatory balance is maintained in these neurons. As NL1B overexpression in post-natal-born neurons selectively increased excitatory synapse density, assessing the effect of NL1B overexpression in post-natal-born neurons on learning and memory performances would give insight on whether keeping a proper excitation/inhibition balance is crucial for maintaining the proper function of the neuronal network.…”
Section: Introductionmentioning
confidence: 66%